(untitled) (Medico Legal Update, 2019)
Introduction: Blunt cardiac injury (BCI) refers to injury sustained due to blunt trauma to the heart. The manifestations of such range from clinically silent, transient arrhythmias to deadly cardiac wall rupture. Objectives: To study the blunt cardiac trauma following vehicular accidents brought for autopsy to the morgue of Osmania Medical College, Hyderabad have been studied. Method: 55 cases of blunt cardiac trauma following vehicular accidents brought for autopsy to the Department of Forensic Medicine , Osmania Medical College, Hyderabad have been studied to find out types of cardiac injuries, their association with sternal and rib fractures, mechanism of causation, risk factors, etc. Results: It was observed that 60 % of the cases with blunt cardiac trauma had associated sternal and rib fractures. Maximum number (58%) of the cardiac rupture was seen in run-over cases. The right ventricle of the heart was involved in 23 (41%) cases . All the injuries were located on the anterior surface of the heart. Conclusion: In assessing blunt cardiac trauma victims in vehicular accidents, knowledge about the commonest sites, types and degrees of injuries have been highlighted in the present study, which will help in a timely intervention.